A política de preços como uma estratégia competitiva para o mercado de flats em Fortaleza - Pinheiro, Flávia Costa (2006)
The objective this project is to establist operational limits of a policy of differentiated princing for different seasons of demanda in hotel enterprises. This policy has iniated from the growth n demand in the Fortaleza market. An economically coherent model is estimated to establish the demand for price that affers a just financial return in the market.The main conclusion of this study is that demand, altough non-eslastic, adjusts to the practice of price differentiation that promote the growth of the “ Receita de Hospedagem” of the avaiable rooms (revpar) in the sector of flats. The calculations used to determine the ideal “revpar” allow for profitability to the manager of a hotel enterprise in that they define the practices that determine the gaia possibilities of the investitor.